Perception Regarding Respectful Maternity Care among Postnatal Mothers at Tertiary Centre Hospital, Koshi Province - Neupane, Saraswata; Pokhrel, Indira; Singh, Rameshwari; Dhakal, Ram Prasad (Journal of Nobel Medical College, 2023)
Background: Pregnancy and childbirth are momentous events, with deeply personal and social significance in the lives of women, families, and communities. Around the world, in every country and community, pregnancy and childbirth are immensely important events in the lives of women and families. So, the study aimed to assess the perception regarding respectful maternity care among postnatal mothers. Materials and Methods: A cross-sectional study was conducted among postnatal mothers at Tertiary Centre Hospital in Koshi Province. The study was started after acquiring approval from the Institutional Review Committee of Nobel Medical College. Data was collected using a face-to-face interview technique with a standardized tool from June 2022 to September 2022. A total of 102 postnatal mothers were taken as a sample by using a non-probability purposive sampling technique. Data analysis was done by descriptive study. Results: A total of 102 respondents participated in the study of which 62.7% had received overall dimensions of experienced Respectful Maternity Care (RMC) with a mean score ± SD (51.91 ± 5.56). Likewise, among the four dimensions of RMC, the highest average mean score of 81.96 is observed in the discrimination-free care with an SD of 11.08, where 100 % of the women claimed being received discrimination-free care. Conclusion: There was a significant association of RMC with residence and the number of ANC visits. Even though RMC prioritizes removing disrespectful and abusive settings from healthcare facilities, one-half of participants felt that they had not utilized all of RMC’s offerings.